Kemampuan Guru Menerapkan Feedback Dalam Pembelajaran Pendidikan Agama Kristen - Yohana Olivia Sitorus; Dorlan Naibaho (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
This research aims to explore teachers' ability to apply feedback in the context of Christian Religious Education learning. Through a qualitative approach, this research seeks sources and reconstructs them from various sources such as books, journals and current research. The results show that teachers' ability to apply effective feedback in Christian religious education learning has a positive impact on students' understanding. The findings highlight the important role of feedback in improving understanding of Christianity concepts. Teachers who are able to provide specific, constructive and well-timed feedback will create meaningful learning.